"AND" luminescent "reactive" molecular logic gates: a gateway to multi-analyte bioimaging and biosensing. Issue 5 (11th December 2014) - Romieu, Anthony
Abstract : This feature article focuses on the recent development of "AND" luminescent molecular logic gates, in which the optical output is produced in response to multiple (bio)chemical inputs and through cascades of covalent bond-modifying reactions triggered by target (bio)analytes, for biosensing and bioimaging applications in complex media. Abstract : This review outlines examples that illustrate a recent and highly innovative concept in the field of (bio)molecular sensing, namely the simultaneous multi-analyte detection using "reactive" luminescent probes that are able to produce an optical signal only in response to multiple (bio)chemical inputs and through covalent chemical reactions with target (bio)analytes. Unlike conventional "AND" molecular logic gates based on supramolecular photochemical mechanisms, these unusual "smart" optical (bio)probes are suitable tools to track the rise and fall of a wider range of biologically relevant analytes, in complex media and with higher selectivity. The potential utility of this concept for in vivo molecular imaging and possible solutions to adapt the described luminogenic processes to far-red or NIR emitters are also discussed.